Enhancing the Economy of Women Weavers (Perempuan Penenun) through Digital Transformation in East Lombok - Yusnidar, Fitri; Sholihah, Qomariyatus; Utaminingsih, Alifiulahtin (Wacana Journal of Social and Humanity Studies, 2026)
This study aims to analyze strategies used to improve the economic conditions of women weavers in Pringgasela Village, East Lombok, through the adoption of digital transformation. A descriptive qualitative approach was employed, with data collected through participatory observation, in-depth interviews, and documentation. The findings indicate that the use of social media, e-commerce platforms, and digital training has successfully increased income and expanded market reach for traditional woven products. Challenges encountered include limited access to technology, low digital literacy, and the need for ongoing support. The study recommends cross-sector collaboration among local governments, educational institutions, and the private sector to build an inclusive and sustainable digital ecosystem for female weavers.   Keywords: Women Weavers, Digital Transformation, Local Economy, Traditional Weaving, Lombok